Global projects and the strange: decolonial studies in Brazilian academic production - Carniel, Fagner (2021)
What is the place of decolonial studies in Brazilian academic production? Does the contemporary circulation of theoretical perspectives that question colonial ontologies and claim a critical renewal for Latin American thought can influence the development of new research agendas in the country? Through a mapping of 246 articles that approached the ‘decolonial’ between 2009 and 2018, the article aims to understand the different uses that the category has acquired in published researches in Portuguese language. Bibliometric and discursive analyses are performed with the intention of presenting an updated table of the main themes, authors and bibliographies that are being proposed by Brazilian researchers in journals that are Scopus and Web of Science indexed. The results of this investigation suggest that decolonial is a plural and under construction category in Brazil, both analytical and political, which is organized around the disciplinary field of the social sciences but impacts the production of knowledge in other areas already.